HCV knowledge and attitudes among HIV-negative MSM and MSM living with HIV in China: results from a cross-sectional online survey - Xu, Wenqian; Zhao, Peizhen; Li, Haiyi; Wang, Cheng (BMC infectious diseases, 2023)
Men who have sex with men (MSM) are at high risk of hepatitis C virus (HCV) infection, especially for those living with human immunodeficiency virus (HIV). Learning about knowledge of and attitudes towards HCV is essential to inform health promotion interventions development. This is one of very limited studies to examine the level of knowledge and attitudes towards HCV and their determinants among HIV-negative MSM and MSM living with HIV in China. A cross-sectional survey was conducted across seven provinces in China from December 2021 to January 2022. All the MSM living with HIV were recruited offline, whereas the recruitment ratio for HIV-negative MSM was half online and half offline. Data on socio-demographic characteristics, sexual behaviors, knowledge about HCV, and attitude towards HCV from participants were collected through the online survey. Univariate and multivariable logistic regressions were used to determine the associated factors. Only 39.3% (33/84) of HIV-negative men and 44.0% (37/84) of men living with HIV had a good level knowledge about HCV. Nearly one-third (32.1%, 27/84) of HIV-negative men and 41.7% (35/84) of men living with HIV reported a positive attitude towards HCV. For HIV-negative men, positive attitude towards HCV was associated with the multiple sexual partners (aOR: 5.8, 95%CI:1.9-18.1) and the use of recreational substances (aOR: 3.1, 95%CI: 1.0-9.4). For men living with HIV, knowledge about HCV was associated with disclosing sexual orientation to healthcare providers, family or friends (aOR: 7.0, 1.9-26.0), the multiple sexual partners (aOR: 0.2, 0.1-1.0), the use of recreational substances (aOR: 3.7, 95%CI: 1.1-13.1) and the HBV testing history (aOR: 7.3, 95%CI: 1.6-32.7); positive attitude towards HCV was associated with the use of recreational substances (aOR: 3.1, 95%CI: 1.1-9.0). The majority of Chinese MSM showed an inadequate knowledge of and negative attitude towards HCV irrespective of HIV infection status. More tailored education campaigns and multicomponent interventions are required to be targeted on MSM, and more researches are also needed to inform how best to address the negative attitudes of this population towards HCV.